Effects of using games in speaking classes on students' speaking performance: A case at a secondary school in Kien Giang province - Tống Kiều Nương (Trường Đại học Trà Vinh, 2024)
Firstly, it aims at investigating the effects of using games in speaking classes on students' speaking performances. Secondly, it explores students’ attitudes towards using games in speaking classes.